The hunt for nonflammable refrigerant blends to replace R-134a. (August 2019) - Bell, Ian H.; Domanski, Piotr A.; McLinden, Mark O.; Linteris, Gregory T.
Abstract: We investigated refrigerant blends as possible low GWP (global warming potential) alternatives for R-134a in an air-conditioning application. We carried out an extensive screening of the binary, ternary, and four-component blends possible among a list of 13 pure refrigerants comprising four hydrofluoroolefins (HFOs), eight hydrofluorocarbons (HFCs), and carbon dioxide. The screening was based on a simplified cycle model, but with the inclusion of pressure drops in the evaporator and condenser. The metrics for the evaluation were nonflammability, low GWP, high COP (coefficient of performance), and a volumetric capacity similar to the R-134a baseline system. While no mixture was ideal in all regards, we identified 16 binary and ternary blends that were nonflammable (based on a new estimation method) and with COP and capacity similar to the R-134a baseline; the tradeoff, however, was a reduction in GWP of, at most, 54% compared to R-134a. An additional seven blends that were estimated to be "marginally flammable" (ASHRAE Standard 34 classification of A2L) were identified with GWP reductions of as much as 99%. These 23 "best" blends were then simulated in a more detailed cycle model.